Substitute Heirs in Article 185 Compilation of Islamic Law Maqashid Shariah Jaser Audah Perspective - Ubaidillah, Ubaidillah; Nurohman, Dede; Anshor, Ahmad Muhtadi; Baihaqi, Wahid Ahtar; Kooria, Mahmood (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2024)
AbstractArticle 185 KHI was established as a reaction to the unequal distribution of inheritance by giving grandchildren the right of replacement for children. In the context of Islamic law reform in Indonesia, the Compilation of Islamic Law (KHI) proposal has sparked endless debate between pros and cons. As far as the researcher observes, the debates expressed in various discussions and research have not been able to resolve this issue, including attempts to interpret Hazairin through theory of mawali. This research aims to describe and analyze maqasid sharia Jaser Audah perspective on the provisions of successor heirs and relevance maqasid sharia Jaser Audah against the benefits found in Article 185 KHI. This research uses a qualitative type that is oriented on purpose. The results of this study show that the view maqasid sharia Jaser Audah regarding the meaning of successor heir can be seen through the following six features: 1) cognitive character: positioning the results of Zayd's ijtihad as a product of ijtihad; 2) universal features: replacement of heirs applies to all parties with consideration of egalitarian principles, distributive justice and empowerment of heirs; 3) characteristics of openness: making internal factors (customary law, family structure) and external (comparative studies and equality) in the genealogy of Article 185 as tradition; 4) hierarchical structure features: the right of succession given to grandchildren philosophically contains benefits that are oriented towards maqsad (goal) which runs simultaneously; 5) include the element of justice as a philosophical value in mediating the hadith narrated by Bukhari and the results of Zayd's ijtihad; 6) the aim of the Islamic law system: granting grandchildren rights over children is an effort to realize them purpose justice, empowerment and protection of human rights.